2006
DOI: 10.3815/000000006784016585
|View full text |Cite
|
Sign up to set email alerts
|

The Making of Britain's First Urban Landscapes: The Case of Late Iron Age and Roman Essex

Abstract: This paper presents preliminary research into the social and economic impact of early urban settlement in Britain, focusing on the case-study area of Late Iron Age to Roman Essex. Through fresh analysis of ceramic assemblages from Colchester and Heybridge, we describe hitherto unrecognised socio-cultural groupings and identities through subtle differences in the deposition of pottery in the generations before and after conquest. The concluding discussion concentrates on problems that we still have to address i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The contrast between the two styles of consumption could not have been greater than at Claudio-Neronian Colchester (AD 49-60), where intra-site analysis of pottery deposition has shown that the inhabitants of the oppidum at post-conquest Sheepen preferred to consume in a manner emphasizing large Gallic drinking vessels, despite access to the material culture of the Roman colonists at Head Street, who eschewed Gallo-Belgic imports in favor of a template of consumption based around dining (Pitts and Perring 2006). It is notable that the 'urban' assemblage with the most statistical similarity with the LPRIA settlements is from the short-lived fortress at Head Street (ColH 3 on Fig.…”
Section: Post-conquest Settlements C Ad 40-200mentioning
confidence: 85%
See 2 more Smart Citations
“…The contrast between the two styles of consumption could not have been greater than at Claudio-Neronian Colchester (AD 49-60), where intra-site analysis of pottery deposition has shown that the inhabitants of the oppidum at post-conquest Sheepen preferred to consume in a manner emphasizing large Gallic drinking vessels, despite access to the material culture of the Roman colonists at Head Street, who eschewed Gallo-Belgic imports in favor of a template of consumption based around dining (Pitts and Perring 2006). It is notable that the 'urban' assemblage with the most statistical similarity with the LPRIA settlements is from the short-lived fortress at Head Street (ColH 3 on Fig.…”
Section: Post-conquest Settlements C Ad 40-200mentioning
confidence: 85%
“…Bourdieu, 1984). Further details of the previous use of the technique with pottery assemblages (Pitts, 2005a(Pitts, ,b,2007aPitts and Perring, 2006) and in the study of the globalization of modern food distribution and consumption can be found elsewhere (Pitts et al, 2007). CA is related to the more popular method of principal components analysis, with the main difference being that CA is better suited to the analysis of categorical variables (e.g.…”
Section: Methods and Datamentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, Roman town planning was not simply down to surveying, engineering and mathematics but involved a variety of rituals and ceremonies in the landscape (Creighton, 2000: 209-13;Pitts and Perring, 2006;Rykwert, 1976: 44-60;Woodward and Woodward, 2004). A town should not be considered simply in terms of a physical entity but as a place that is shaped, invented and conceptualized by social actors over time (Lefebvre, 1991: 73) and, in Britain at least, this is likely to have been influenced by meaning-laden space in the pre-Roman period.…”
Section: ■ Studying the Roman Town And Its Location In Britainmentioning
confidence: 99%
“…As a great deal of literature attests, 26 it is problematic to draw direct correlations between static artefacts and the dynamic, shifting, and multifaceted process of the elaboration of identity. 25 Pitts and Perring 2006;Perring and Pitts 2013, 232-38. This is especially pertinent to the debate over urban origins.…”
Section: Britain's First Towns: Scholarship and Debatementioning
confidence: 99%